Malaysian apparel e-shoppers : a behavioural study of online consumers at University Malaysia Kelantan - Naila Aaijaz; Mohamed Dahlan Ibrahim (2010)
The objective of this paper is to study factors that affect potential online sales of specific product. In short, this study investigates consumer online behaviour, potential of online sales to identify those factors that influence online potential sales of a specific product by developing an instrument for investigating and understanding consumer's online apparel shopping behaviour of undergraduate student and staff at the University Malaysia Kelantan (UMK) located in the state of Kelantan, Malaysia. Customer's attitude towards online shopping is the key to the survival and profitability of internet retailers in the intensely competitive market. A five-level Likert scale ranging from one (strongly disagree) to five (strongly agree) was used to generate result for this research, and to make us understand more about online shopping, in order to determine attitudes towards online shopping. A self-administrated questionnaire, based on shopping orientation, perceived benefits, and attitude was developed. The sample population of this study consisted of fifty undergraduate students and fifty staff of University Malaysia Kelantan who were selected by using random sampling method and involved in the research study. The questionnaire consisted of four components. Out of the four components, one component referred to demographic question and three components referred to online shopping orientation, online shopping perceived benefits and attitude towards online shopping. The reliability of data and scale was tested by computing factor analysis, descriptive analysis and a reliability test. This instrument is offered to the research community as a tool that may be used in conducting future research related to online shopping behaviour.